Pemahaman Hadis Kebersihan Lingkungan dan Relevansinya dengan Konsep Zero Waste - Bastari, Ahmad (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This article aims to discuss the understanding of hadith regarding environmental cleanliness, directed towards finding its relevance to the zero waste concept, which is a principle aimed at reducing waste to zero, leading to better environmental management. This concept not only focuses on the collection of waste in specific locations but also aims to decrease the ever-increasing amount of waste. The article employs a qualitative method, utilizing library research and descriptive-analytical data analysis. Consequently, the article concludes that the understanding of hadith on environmental cleanliness has a strong relevance to the zero waste concept, as both share the same objectives. This is evident from the vision of zero waste, which emphasizes waste reduction and transportation in alignment with the hadiths on environmental cleanliness. This relevance encourages environmental awareness by minimizing waste in public spaces, homes, rivers, and land. Therefore, it is not an exaggeration to state that the zero waste concept can be regarded as an implementation of the hadiths on environmental cleanliness.